Motivation for a career in dentistry: the views of dental students in the United Arab Emirates. (3rd June 2013) - Rashid, Hazim; Manoharan, Andiappan; Abufanas, Salem; Gallagher, Jennifer Elizabeth
Abstract : Objectives: To investigate final‐year dental students' perceived motivation for choosing dentistry as a professional career at one dental school in the United Arab Emirates (UAE). Method: Final‐year dental students of Ajman University ( n  = 87) completed a questionnaire. Univariate and multivariate analysis of the data were undertaken using statistical software. Results: A response rate of 82% ( n  = 71) was achieved, 65% of whom were female. Students ranged from 21 to 29 years of age. Motivation to study dentistry was led by a 'desire to work in health care' (93%), 'wish to provide a public service' (88.7%) and because 'degree leads to a recognised job' (84.5%). Males were significantly more likely to report 'high income' (84% vs . 67%; P  =   0.01) and females 'influence of family' (80% vs . 60%; P  =   0.02) as motivating influences. The reliability and internal consistency of the instrument as calculated by Cronbach's alpha was 0.82. Eight factors explaining the 71% of the variation were: 'professional job factors' (11.7%), 'experience and advice' (9.8%), 'business and financial with independence' (9.7%), 'careers, advice and possibilities' (8.9%), 'knowledge and job security' (8.8%), 'health care, people and public service' (8%), 'family and friends' (7.2%) and 'career in dentistry' (6.9%). Gender was a significant predictor of 'business and financial' factor ( b  = −0.76; P  =   0.003) and age for 'careers in dentistry' ( b  = −0.18; P  =   0.03). Conclusion: Students are motivated by a wide range of factors similar to those found in other studies; however, business features and family influences were significantly associated with gender.